Political thought in Medieval times - Morrall, John B. (London, 1958)
This is the first attempt in English to give a short yet comprehensive. account of political thought in medieval times. The period dealt with extends from the last years of the Roman Empire to the early years of the sixteenth century. The primary aim of the book is to present medieval political thought against the historical background which animated it. The great thinkers of the period are studied in some detail but the main emphasis is on the currents of thought and action in which it individuals and institutions played their part. The central theme of the whole treatment at is the growth of the characteristically medieval conception of a religio-political common wealth and the gradual replacement of that conception by the idea of the State.
Keywords: Political science